A BRIEF PHILOSOPHICAL-SCIENTIFIC ANALYSIS OF MAKOMS - Dilshodjon Toshaliev (Galaxy International Interdisciplinary Research Journal, 2021)
The article briefly reveals the essence of the philosophical content of the art of the Uzbek national maqom and the importance of philosophical and scientific analysis in the study of maqom and the peculiarities of the melodic structure of the branches of the maqom.